FeNiP@NPC composite material, and preparation method and application thereof

CN122907571APending Publication Date: 2026-10-13ZHEJIANG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610925401.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0004]然而,尽管上述专利所制备的催化剂已展现出较为优异的催化性能,但随着锌-空气电池技术的持续迭代升级,行业对催化剂的活性、稳定性及双功能匹配性提出了更高要求,仍具备优化与突破的空间

Benefits of technology

[0017]本申请通过溶剂热制备FeNi双金属有机配位前驱体,结合原位聚苯胺-植酸包覆与ZIF-8复合碳化,成功构筑FeNiP纳米颗粒均匀镶嵌于N/P共掺杂多孔碳的FeNiP@NPC复合材料,该材料具有分级多孔结构与高比表面积,可充分暴露活性位点、优化电子结构与三相界面传质,在碱性体系中表现出优异的ORR/OER双功能电催化活性,ORR起始电位0.95V、半波电位0.86V、极限电流密度6.68mA·cm-2,优于商用Pt/C,OER在10mA·cm-2电流密度下过电位仅420mV,双功能电位差ΔE低至0.78V,以其作为空气阴极的可充电锌-空气电池实现更高功率密度、更大放电比容量与更长循环稳定性,且无需使用贵金属、原料成本低、制备工艺可控,综合性能与产业化前景显著优于现有非贵金属催化剂与传统贵金属体系,为高性能、低成本锌-空气电池电催化剂的开发提供了高效解决方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907571A_ABST
    Figure CN122907571A_ABST
Patent Text Reader

Abstract

This application belongs to the field of zinc-air battery technology, specifically relating to a FeNiP composite material, its preparation method, and its application. This application successfully constructs a FeNi@NPC composite material with FeNiP nanoparticles uniformly embedded in N / P co-doped porous carbon by solvothermal preparation of a FeNi bimetallic organic coordination precursor, combined with in-situ polyaniline-phytic acid coating and ZIF-8 composite carbonization. This material possesses a hierarchical porous structure and high specific surface area, which can fully expose active sites, optimize electronic structure and three-phase interface mass transfer, and exhibit excellent ORR / OER bifunctional electrocatalytic activity in alkaline systems, with an ORR onset potential of 0.95V, a half-wave potential of 0.86V, and a limiting current density of 6.68 mA·cm⁻¹. ‑2 Superior to commercial Pt / C, OER at 10 mA·cm ‑2 With an overpotential of only 420mV at current density and a dual-function potential difference ΔE as low as 0.78V, rechargeable zinc-air batteries using this as an air cathode achieve higher power density, greater discharge specific capacity, and longer cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of zinc-air battery electrocatalyst composite materials, specifically to an iron-nickel-phosphorus based composite material with dual electrocatalytic activity for both oxygen reduction and oxygen evolution. Background Technology

[0002] With the continuous growth of global energy demand, rechargeable zinc-air batteries have become a core technology with great potential in the field of new energy storage due to their advantages such as ultra-high energy density, abundant resources, and environmental friendliness. The energy cycle of zinc-air batteries is completed by the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the cathode: during discharge, the cathode catalyzes ORR, reducing oxygen to hydroxide ions and releasing electrons; during charging, it drives OER, oxidizing hydroxide ions to oxygen. However, both ORR and OER are multi-electron transfer reactions, with complex intermediate transformations and high activation energy barriers, resulting in slow reaction kinetics, high overpotentials, and significantly low exchange current density at the cathode in the two reactions, which seriously restricts battery performance. Currently, noble metal catalysts such as Pt / C, IrO2, and RuO2 are still the best performing oxygen electrocatalysts, but they suffer from insufficient bifunctional activity, poor long-term stability, scarcity of raw materials, and high cost, making it difficult to meet the needs of large-scale application of zinc-air batteries. Therefore, developing low-cost, high-activity, and high-stability ORR / OER bifunctional non-noble metal electrocatalysts is crucial for constructing efficient rechargeable zinc-air battery systems.

[0003] To further improve the overall performance of rechargeable zinc-air batteries, extensive research has been conducted in the field of transition metal phosphide catalytic materials. Among them, patent application number 202510596147.X discloses a hollow carbon nanotube-supported bimetallic heterophosphide electrocatalyst. This technology uses aniline as the nitrogen source and phytic acid as the phosphorus source, employing methyl orange as a soft template to prepare a hollow polyaniline-phytic acid copolymer. The strong chelating effect of phytic acid on metal ions adsorbs iron and cobalt sources. After high-temperature calcination, a hollow carbon nanotube-supported Fe2P / Co2P heterophosphide composite material is generated in situ, and this composite material is applied to ORR / OER bifunctional electrocatalysis. Electrochemical testing results show that this catalyst exhibits excellent oxygen electrocatalytic performance. As an ORR catalyst, the onset potential is 0.97V, the half-wave potential is 0.83V, and the limiting current density reaches 4.50 mA / cm². -2 When used as an OER catalyst, at 10 mA / cm² -2 The overpotential at the current density is only 430mV, exhibiting good bifunctional catalytic activity, which provides a useful reference for the design of air cathode materials for zinc-air batteries.

[0004] However, although the catalysts prepared by the aforementioned patents have shown relatively excellent catalytic performance, with the continuous iteration and upgrading of zinc-air battery technology, the industry has put forward higher requirements for the activity, stability and bifunctional matching of catalysts, and there is still room for optimization and breakthroughs. Summary of the Invention

[0005] The purpose of this application is to provide a FeNiP@NPC composite material with better ORR / OER bifunctional electrocatalytic effect, which is achieved through the following technical solution:

[0006] A method for preparing FeNiP@NPC composite material includes the following steps: S1, dissolving an iron source, a nickel source, and an organic ligand in a solvent and carrying out a solvothermal reaction to obtain an iron-nickel-containing organometallic coordination precursor; S2, mixing the organometallic coordination precursor, an acidic phosphorus source, aniline, and an aniline polymerization oxidative initiator to obtain a composite modified precursor; S3, mixing the composite modified precursor with a zeolite imidazole ester framework material and calcining it under an inert atmosphere to obtain the FeNiP@NPC composite material.

[0007] Preferably, the iron source is ferric nitrate nonahydrate, the nickel source is nickel nitrate hexahydrate, and the organic ligand is 2-aminoterephthalic acid; the molar ratio of ferric nitrate nonahydrate, nickel nitrate hexahydrate and 2-aminoterephthalic acid is (1~2):(0.5~2):(1~1.5).

[0008] Preferably, the acidic phosphorus source is phytic acid, and the aniline polymerization oxidative initiator is ammonium persulfate.

[0009] Preferably, the volume-to-mass ratio of phytic acid, aniline and ammonium persulfate is (250~300) μL: (450~550) μL: (650~750) mg.

[0010] Preferably, step S2 further includes: first dispersing the organometallic coordination precursor and sodium dodecylbenzenesulfonate in deionized water, and then adding phytic acid, aniline and ammonium persulfate.

[0011] Preferably, the mass ratio of the organometallic coordination precursor, sodium dodecylbenzenesulfonate and ammonium persulfate is (20~30):(60~65):(80~95).

[0012] Preferably, the zeolite imidazole ester skeleton material is ZIF-8, and the mass ratio of the composite modified precursor to the zeolite imidazole ester skeleton material is 1:(7~10).

[0013] Preferably, the calcination is a segmented calcination, specifically: the temperature is increased from room temperature to 500-600℃ at a heating rate of 5-10℃ / min and held for 1-1.5h, then the temperature is increased to 900-1000℃ and held for 1.5-2.5h, and the calcination atmosphere is nitrogen.

[0014] A FeNiP@NPC composite material is prepared using any of the preparation methods described above.

[0015] Application of any of the above-mentioned FeNiP@NPC composite materials in zinc-air batteries.

[0016] Compared with the prior art, this application has the following beneficial effects:

[0017] This application successfully constructed a FeNiP@NPC composite material by solvothermal preparation of a FeNi bimetallic organic coordination precursor, combined with in-situ polyaniline-phytic acid coating and ZIF-8 composite carbonization. FeNiP nanoparticles were uniformly embedded in N / P co-doped porous carbon. This material possesses a hierarchical porous structure and high specific surface area, which fully exposes active sites, optimizes electronic structure and three-phase interface mass transfer, and exhibits excellent ORR / OER bifunctional electrocatalytic activity in alkaline systems, with an ORR onset potential of 0.95 V, a half-wave potential of 0.86 V, and a limiting current density of 6.68 mA·cm⁻¹. -2 Superior to commercial Pt / C, OER at 10 mA·cm -2 With an overpotential of only 420mV at current density and a bifunctional potential difference ΔE as low as 0.78V, rechargeable zinc-air batteries using this as an air cathode achieve higher power density, greater discharge specific capacity, and longer cycle stability. Moreover, it does not require the use of precious metals, has low raw material costs, and a controllable preparation process. Its overall performance and industrialization prospects are significantly better than existing non-precious metal catalysts and traditional precious metal systems, providing an efficient solution for the development of high-performance, low-cost zinc-air battery electrocatalysts. Attached Figure Description

[0018] The attached diagram will be briefly described below:

[0019] Figure 1 Transmission electron microscope and high-resolution transmission electron microscope images of FeNiP@NPC composite material;

[0020] Figure 2 X-ray diffraction patterns of FeNiP@NPC composites with different Fe / Ni ratios;

[0021] Figure 3 Nitrogen isothermal adsorption-desorption curves and pore size distribution curves of FeNiP@NPC composite material;

[0022] Figure 4The X-ray photoelectron spectrum of FeNiP@NPC composite material includes the full spectrum and high-resolution spectra of C1s, N1s, Ni2p, and P2p.

[0023] Figure 5 The electrochemical performance of FeNiP@NPC composite material in the oxygen reduction reaction in an alkaline system is shown in the following figures: (a) cyclic voltammetry curves; (b) linear sweep voltammetry polarization curves; (c) comparison of kinetic current density at half-wave potential and 0.8V potential; (d) Tafel slope curves.

[0024] Figure 6 The following are the bifunctional electrocatalytic performance curves of FeNiP@NPC composites for oxygen reduction and oxygen evolution, including: (a) oxygen reduction polarization curves of FeNiP@NPC (Fe:Ni=2:1) ​​at different rotation speeds; (b) comparison of electron transfer number and hydrogen peroxide yield of FeNiP@NPC composites with different Fe / Ni ratios and Pt / C; (c) oxygen evolution polarization curves; and (d) ORR / OER bifunctional linear sweep voltammetric curves of each FeNiP@NPC composite at 1600 rpm.

[0025] Figure 7 The electrochemical active surface area characterization diagrams for FeNiP@NPC composites are shown, where: (a–c) are cyclic voltammetry curves at different scan rates within the non-Radida potential range; (d) are the calculated results of the double-layer capacitance Cdl of FeNiP@NPC composites with different Fe / Ni ratios.

[0026] Figure 8 The graph shows the electrochemical performance of a rechargeable zinc-air battery with FeNiP@NPC as the air cathode. Detailed Implementation

[0027] The present application will now be further described by way of specific embodiments. Those skilled in the art will be able to implement the present application based on these descriptions. Furthermore, the embodiments of the present application described below are generally only a part of the embodiments of the present application, and not all of the embodiments. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present application without inventive effort should fall within the scope of protection of the present application.

[0028] Example 1

[0029] This embodiment discloses a method for preparing FeNiP@NPC (Fe:Ni=2:1) ​​composite material, specifically including the following steps:

[0030] (1) Preparation of ZIF-8

[0031] 4.76 g of zinc nitrate hexahydrate was dissolved in 120 mL of methanol to obtain solution A; 4.52 g of dimethylimidazole was dissolved in 120 mL of methanol to obtain solution B. Solution A was slowly poured into solution B, and the mixture was stirred for 24 h. After the reaction was completed, the mixture was washed several times by centrifugation with methanol and dried in a vacuum oven at 60 °C to obtain ZIF-8 powder.

[0032] (2) Preparation of metal-organic coordination precursors

[0033] 1.66 mmol of ferric nitrate nonahydrate, 0.833 mmol of nickel nitrate hexahydrate, and 1.25 mmol of 2-aminoterephthalic acid were dissolved in 15 mL of DMF. After complete dissolution, the solution was transferred to a polytetrafluoroethylene-lined reactor and reacted solvothermically at 110 °C for 12 h. After natural cooling to room temperature, the solution was washed several times by centrifugation with DMF and ethanol, and dried under vacuum at 60 °C to obtain an iron-nickel-containing organometallic coordination precursor.

[0034] (3) Preparation of composite modified precursor

[0035] Take 200 mg of the above organometallic coordination precursor and 504 mg of sodium dodecylbenzenesulfonate, disperse them in 80 mL of deionized water, and stir for 4 h until uniformly dispersed; then add 500 μL of aniline, 280 μL of phytic acid and 704 mg of ammonium persulfate in sequence, and continue to stir the reaction for 2 h. After the reaction is completed, wash several times with deionized water and dry under vacuum at 60 °C to obtain the composite modified precursor.

[0036] (4) Preparation of FeNiP@NPC composite material by calcination

[0037] The above-mentioned composite modified precursor and ZIF-8 were ground and mixed evenly at a mass ratio of 1:8, and placed in a tube furnace under nitrogen atmosphere. The temperature was increased from room temperature to 500℃ at a heating rate of 5℃·min⁻¹, held for 1h, and then increased to 900℃ and held for 2h. The mixture was then naturally cooled to room temperature to obtain the FeNiP@NPC (Fe:Ni=2:1) ​​composite material.

[0038] Example 2

[0039] This embodiment discloses a method for preparing FeNiP@NPC (Fe:Ni=1:1) composite material, specifically including the following steps:

[0040] (1) Preparation of ZIF-8

[0041] 4.76 g of zinc nitrate hexahydrate was dissolved in 120 mL of methanol to obtain solution A; 4.52 g of dimethylimidazole was dissolved in 120 mL of methanol to obtain solution B. Solution A was slowly poured into solution B, and the mixture was stirred for 24 h. After the reaction was completed, the mixture was washed several times by centrifugation with methanol and dried in a vacuum oven at 60 °C to obtain ZIF-8 powder.

[0042] (2) Preparation of metal-organic coordination precursors

[0043] 1.66 mmol of ferric nitrate nonahydrate, 1.66 mmol of nickel nitrate hexahydrate, and 1.25 mmol of 2-aminoterephthalic acid were dissolved in 15 mL of DMF. After complete dissolution, the solution was transferred to a polytetrafluoroethylene-lined reactor and reacted solvothermically at 110 °C for 12 h. After natural cooling to room temperature, the solution was washed several times by centrifugation with DMF and ethanol, and dried under vacuum at 60 °C to obtain an iron-nickel-containing organometallic coordination precursor.

[0044] (3) Preparation of composite modified precursor

[0045] Take 200 mg of the above organometallic coordination precursor and 504 mg of sodium dodecylbenzenesulfonate, disperse them in 80 mL of deionized water, and stir for 4 h until uniformly dispersed; then add 500 μL of aniline, 280 μL of phytic acid and 704 mg of ammonium persulfate in sequence, and continue to stir the reaction for 2 h. After the reaction is completed, wash several times with deionized water and dry under vacuum at 60 °C to obtain the composite modified precursor.

[0046] (4) Preparation of FeNiP@NPC composite material by calcination

[0047] The above-mentioned composite modified precursor and ZIF-8 were ground and mixed evenly at a mass ratio of 1:8, and placed in a tube furnace under nitrogen atmosphere. The temperature was increased from room temperature to 500℃ at a heating rate of 5℃·min⁻¹, held for 1h, and then increased to 900℃ and held for 2h. The mixture was then naturally cooled to room temperature to obtain the FeNiP@NPC (Fe:Ni=1:1) composite material.

[0048] Example 3

[0049] This embodiment discloses a method for preparing FeNiP@NPC (Fe:Ni=1:2) composite material, specifically including the following steps:

[0050] (1) Preparation of ZIF-8

[0051] 4.76 g of zinc nitrate hexahydrate was dissolved in 120 mL of methanol to obtain solution A; 4.52 g of dimethylimidazole was dissolved in 120 mL of methanol to obtain solution B. Solution A was slowly poured into solution B, and the mixture was stirred for 24 h. After the reaction was completed, the mixture was washed several times by centrifugation with methanol and dried in a vacuum oven at 60 °C to obtain ZIF-8 powder.

[0052] (2) Preparation of metal-organic coordination precursors

[0053] 1.66 mmol of ferric nitrate nonahydrate, 3.32 mmol of nickel nitrate hexahydrate, and 1.25 mmol of 2-aminoterephthalic acid were dissolved in 15 mL of DMF. After complete dissolution, the solution was transferred to a polytetrafluoroethylene-lined reactor and reacted solvothermically at 110 °C for 12 h. After natural cooling to room temperature, the solution was washed several times by centrifugation with DMF and ethanol, and dried under vacuum at 60 °C to obtain an iron-nickel-containing organometallic coordination precursor.

[0054] (3) Preparation of composite modified precursor

[0055] Take 200 mg of the above organometallic coordination precursor and 504 mg of sodium dodecylbenzenesulfonate, disperse them in 80 mL of deionized water, and stir for 4 h until uniformly dispersed; then add 500 μL of aniline, 280 μL of phytic acid and 704 mg of ammonium persulfate in sequence, and continue to stir the reaction for 2 h. After the reaction is completed, wash several times with deionized water and dry under vacuum at 60 °C to obtain the composite modified precursor.

[0056] (4) Preparation of FeNiP@NPC composite material by calcination

[0057] The above-mentioned composite modified precursor and ZIF-8 were ground and mixed evenly at a mass ratio of 1:8, and placed in a tube furnace under nitrogen atmosphere. The temperature was increased from room temperature to 500℃ at a heating rate of 5℃·min⁻¹, held for 1h, and then increased to 900℃ and held for 2h. The mixture was then naturally cooled to room temperature to obtain the FeNiP@NPC (Fe:Ni=1:2) composite material.

[0058] Performance Test 1

[0059] This performance test physically characterized the FeNiP@NPC composite material prepared in the examples, using the following methods: Scanning electron microscopy (SEM, SU8100, HITACHI, Japan) was used to examine the morphology and surface elemental distribution of the samples. Transmission electron microscopy (TEM, Tecnai G2F20, FEI, Netherlands) was used to examine the fine internal structure of the samples. X-ray diffraction (XRD, D8 Advanced, Bruker AXS, Germany) was used to obtain the internal crystal structure of the material. Nitrogen isothermal adsorption-desorption (ASAP2460, Micromeritics, USA) was used to analyze the specific surface area and pore size distribution of the material. Raman spectroscopy (Raman Evolution, Horiba, France) was used for qualitative analysis of the samples. X-ray photoelectron spectroscopy (K-Alpha, Thermo Fisher Scientific, USA) was used to determine the surface elemental composition and chemical valence state of the material.

[0060] The morphology and structure of the FeNiP@NPC composite material prepared in Example 1 were characterized using transmission electron microscopy. Figure 1As shown in a and b, the sample maintains the regular dodecahedral structure derived from ZIF-8, with a particle size of about 500 nm. The surface is rough and forms a hollow feature. FeNiP nanoparticles are uniformly loaded on the carbon framework. Figure 1 (df) HRTEM images show that the 0.36 nm lattice fringes correspond to highly graphitized carbon, and the 0.149 nm, 0.206 nm, and 0.223 nm fringes correspond to the (210), (201), and (111) crystal planes of FeNiP, respectively, proving that FeNiP was successfully composited with nitrogen-doped porous carbon. EDS surface scanning shows that C, N, P, Fe, and Ni elements are uniformly distributed, and the Fe, Ni, and P signals are highly overlapping, confirming the successful preparation of the FeNiP@NPC catalyst. Local Fe-rich microregions exist in the Fe:Ni=2:1 sample, which can form heterogeneous interfaces with the main FeNiP phase and regulate the adsorption of oxygen intermediates, which is key to improving catalytic activity. The differences in local composition and interfacial synergy caused by different iron-nickel ratios determine the differences in the electrocatalytic performance of the catalysts.

[0061] The phase composition and crystal structure of the FeNiP@NPC composite materials prepared in Examples 1-3 were analyzed using X-ray diffraction (XRD). Figure 2 As shown, the diffraction peak positions of samples with different Fe / Ni ratios are basically consistent, with characteristic peaks located at 40.38°, 44.26°, 47.33° and 57.27°, corresponding to the (111), (201), (210) and (300) crystal planes of hexagonal FeNiP (PDF-93-063-2936). The broad peak at 26° is attributed to the (002) crystal plane of graphite carbon, confirming the successful preparation of the FeNiP@NPC catalyst. The FeNiP lattice has a limit to the solid solution of Fe. When there is excess iron in the system, the excess Fe is difficult to completely enter the lattice and is only distributed on the surface or in the carbon support as ultrafine clusters or low-crystallinity Fe-rich species. Due to their small grain size and low content, there are no obvious diffraction peaks in the XRD pattern, and the main crystal phase characteristics are not changed.

[0062] The specific surface area and pore structure of the FeNiP@NPC composite material prepared in Example 1 were analyzed using nitrogen isothermal adsorption-desorption. Figure 3 As shown in figure a, FeNiP@NPC exhibits a type IV adsorption isotherm. The adsorption capacity increases significantly in the low-pressure region (P / P0 < 0.01), indicating that the material is rich in micropores. An H4-type hysteresis loop appears in the medium-pressure region (P / P0 = 0.5–1.0), confirming the presence of a mesoporous structure. The adsorption capacity increases sharply in the high-pressure region (P / P0 > 0.9), indicating the presence of some macropores. Overall, it is a hierarchical porous structure of micropores–mesopores–macropores. BET calculations show that the catalyst has a specific surface area as high as 832.92 m². 2 g -1 The high specific surface area and multi-level pores can fully expose active sites, accelerate mass transfer, and significantly improve electrochemical performance.

[0063] The surface elemental composition and chemical valence state of the FeNiP@NPC composite material prepared in Example 1 were analyzed using X-ray photoelectron spectroscopy (XPS). Figure 4 As shown, the sample surface contains six elements: Fe, Ni, C, N, O, and P. The C1s spectrum can be fitted with four peaks: CC / C=C, CP, CN, and OC=O. The presence of CP and CN bonds confirms that N and P have been successfully incorporated into the carbon lattice, which can enhance the binding force between FeNiP and the carbon support and effectively regulate the electronic structure. The N1s spectrum consists of pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen, and nitrogen oxides. Pyridine nitrogen and graphitic nitrogen are the main active sites, which can improve the electrocatalytic activity of the material. The Ni2p spectrum shows Ni-P bond and Ni ion state peaks, indicating the formation of Ni-N bonds, proving that there is a strong interaction between FeNiP and the carbon matrix, which is conducive to rapid electron transfer. The P2p spectrum can be fitted with CP and MP bonds, further confirming the effective doping of phosphorus. N and P co-doping can adjust the charge distribution and spin density of the carbon support, significantly improving the electrochemical performance of the catalyst.

[0064] Performance Test 2

[0065] This performance test electrochemically characterized the FeNiP@NPC composite material prepared in the examples. The specific methods are as follows: Electrochemical tests were conducted using a German Zahner electrochemical workstation with a standard three-electrode system equipped with a rotating disk electrode system. The tests were performed at room temperature, using a graphite rod as the counter electrode, Hg / HgO as the reference electrode, and a 0.1M potassium hydroxide aqueous solution as the electrolyte. During the test, all electrode potentials were converted to the reversible hydrogen electrode potential and calculated using formula (1).

[0066]

[0067] Before the test, the electrolyte solution was purged with high-purity Ar / O2 for 30 min, and Ar / O2 saturation was maintained throughout the measurement process. Cyclic voltammetry (CV) (based on Hg / HgO) was recorded within a potential window of -0.8 to 0.2 V at a scan rate of 50 mV / s. -1 .

[0068] ORR test: The ORR activity of the synthesized samples was tested in an oxygen-saturated 0.1 MkOH electrolyte. Electron transfer number (n) and kinetic current density (J) were also measured. k The slope and intercept of the curve fitted by the Koutecky-Levich (KL) equation can be obtained and calculated using formulas (2) and (3):

[0069]

[0070]

[0071] Where J, J K and J L These represent the actual current density, kinetic current density, and limiting diffusion current density, respectively, where F is the Faraday constant (96485 Cmol). -1 ), C o The bulk density of O2 is 1.2 × 10⁻⁶. -3 molL -1 ), D o The diffusion coefficient of O2 is 1.9 × 10⁻⁶. -5 cm 2 s -1 ν is the kinetic viscosity of the electrolyte (0.01 cm⁻¹). 2 s -1 ω is the angular velocity of the rotating electrode (ω=2πr, r is the linear rotational speed).

[0072] The yield and electron transfer number of the ORR intermediate hydrogen peroxide can be measured using a rotating ring-disk electrode. Here, N is the current collection coefficient of the Pt ring in the RRED electrode (0.37), and I... d For disk current, I r The current is the ring current. During the test, a constant potential of 1.37V (vs. RHE) was applied to the ring electrode, and the rotation speed was 2500 rpm. The yield of H2O2 and n can be calculated from (4) and (5):

[0073]

[0074]

[0075] The FeNiP@NPC composite material prepared in the examples was evaluated using the methods described above.

[0076] like Figure 5 As shown in Figure a, FeNiP@NPC (Fe:Ni=2:1) ​​exhibits a distinct reduction peak at 0.8 V in O2-saturated electrolyte, while showing no reduction peak under Ar atmosphere, demonstrating its good oxygen reduction catalytic ability. Figure 5 b indicates that the sample's ORR onset potential is 0.95V, half-wave potential is 0.86V, and limiting current density is 6.68mA·cm⁻¹. -2 All of these are superior to commercial Pt / C. For example... Figure 5 As shown in c, its kinetic current density reaches 33.57 mA·cm at 0.8 V. -2 The Tafel slope is the highest among the three sample groups. Figure 5 d) The values ​​were 68.56, 82.4, 75.4, and 70.87 mV·dec, respectively. -1The slope of FeNiP@NPC (Fe:Ni=2:1) ​​is the lowest, indicating that its ORR reaction kinetics are the fastest.

[0077] LSV tests were performed on FeNiP@NPC (Fe:Ni=2:1) ​​at rotational speeds of 400-1600 rpm to analyze its ORR kinetics and reaction pathway. Figure 6 As shown in (a), the limiting current density increases linearly with increasing rotational speed. KL fitting results indicate that the electron transfer number is 4, following an efficient four-electron oxygen reduction mechanism. RRDE testing further verifies that within the potential range of 0.3-0.8V, the electron transfer number remains between 3.9 and 4.0, the hydrogen peroxide yield is less than 15%, and the overall performance is close to that of Pt / C.

[0078] This performance test also tested the catalyst's OER performance, such as... Figure 6 As shown in Figure c, at a current density of 10 mA·cm⁻², the overpotential of FeNiP@NPC (Fe:Ni=2:1) ​​is 420 mV, demonstrating excellent performance. Figure 6 As shown in Figure d, the ORR / OER bifunctional potential difference ΔE of this catalyst is 0.78V, exhibiting excellent bifunctional electrocatalytic activity. Its superior performance stems from its unique electronic structure and microstructure. The heterogeneous interface optimizes the electronic states of active sites, lowering the reaction energy barrier. The hierarchical porous structure enhances the electrochemical active area and mass transfer efficiency. The strong interaction between the catalyst and the carbon support inhibits particle aggregation and dissolution, improving stability.

[0079] The electrochemically active surface area of ​​the catalyst was evaluated using the double-layer capacitance Cdl, such as... Figure 7 As shown, the Cdl value of FeNiP@NPC (Fe:Ni=2:1) ​​is 25.4 mF·cm⁻², the highest among the three groups of samples, corresponding to the highest electrochemically active surface area. The high specific surface area effectively inhibits the aggregation of FeNiP nanoparticles, increases the number of active sites, and the abundant pore structure provides channels for electrolyte diffusion, promoting efficient catalytic reactions at the oxygen-electrolyte-catalyst three-phase interface.

[0080] Performance Test 3

[0081] This performance test examines the application performance of the FeNiP@NPC composite material prepared in the examples for zinc-air battery applications. First, the air electrode was prepared by diluting a 60wt% polytetrafluoroethylene (PTFE) emulsion to 3% by mass, thoroughly impregnating Toray carbon paper (Toray TGP-H-060), and then treating it at 350°C for 1 hour in a muffle furnace. A slurry of carbon black (Vulcan XC-72R) and PTFE at a mass ratio of 3:2 was prepared and coated onto the treated carbon paper to obtain the gas diffusion layer (GDL). The carbon black loading was 1 mg·cm³. -2The catalyst slurry was then uniformly coated onto the surface of the GDL as an air electrode, with a catalyst loading of 0.5 mg·cm⁻¹. -2 .

[0082] In assembling the zinc-air battery, hydrophobic carbon paper with a catalyst supported was used as the air cathode, a zinc sheet as the anode, and 6MKOH solution as the electrolyte. Electrodes were prepared using a 1:1 mass ratio of Pt / C and IrO2 noble metal catalysts under the same process as a control. Charge-discharge polarization curves of the zinc-air battery were acquired using a Zahner electrochemical workstation, with the open-circuit voltage as the starting voltage and a scan rate of 5 mV·s. -1 The power density was normalized according to the electrode geometry; the catalyst stability was tested using constant current charge-discharge cycles, with the current density set at 10 mA·cm². -2 Each cycle lasts 10 minutes, with 5 minutes each for charging and discharging.

[0083] like Figure 8 As shown in Figure a, the current densities of FeNiP@NPC (Fe:Ni=2:1), FeNiP@NPC (Fe:Ni=1:1), FeNiP@NPC (Fe:Ni=1:2), and Pt / C at 1.0V are 147.9, 45.4, 53.7, and 100.7 mA·cm⁻¹, respectively. -2 Among them, FeNiP@NPC (Fe:Ni=2:1) ​​has the highest current density and the best discharge performance. For example... Figure 8 As shown in b, the highest power density of the zinc-air battery based on FeNiP@NPC (Fe:Ni=2:1) ​​can reach 198.5 mW·cm⁻¹. -2 At 2~50 mA·cm -2 Constant current discharge tests were performed within the current density range, such as... Figure 8 As shown in Figure c, FeNiP@NPC (Fe:Ni=2:1) ​​exhibits a stable discharge voltage plateau, and the voltage can recover to its initial value after current density correction, demonstrating excellent rate performance and reversibility. Figure 8 As shown in d, the battery has a discharge specific capacity as high as 831.82 mAh·g. -1 It is superior to Pt / C-based batteries.

[0084] At 10mA·cm -2Constant current charge-discharge cycle tests were conducted, and FeNiP@NPC (Fe:Ni=2:1) ​​could stably operate for 400 cycles without significant voltage decay, demonstrating excellent cycle stability. The hierarchical porous structure and carbon shell coating of FeNiP@NPC (Fe:Ni=2:1) ​​provide continuous electron transport and mass diffusion channels for the ORR / OER process, while effectively suppressing catalyst particle agglomeration and metal dissolution, thus enabling the zinc-air battery to exhibit excellent discharge performance, rate performance, and cycle stability.

Claims

1. A method for preparing FeNiP@NPC composite material, characterized in that, Includes the following steps: S1. Iron source, nickel source and organic ligand are dissolved in solvent and subjected to solvothermal reaction to obtain iron-nickel metal-organic coordination precursor; S2. Metal-organic coordination precursor, acidic phosphorus source, aniline and aniline polymerization oxidative initiator are mixed to obtain composite modified precursor; S3. The composite modified precursor is mixed with zeolite imidazole ester skeleton material and calcined under an inert atmosphere to obtain FeNiP@NPC composite material.

2. The method for preparing a FeNiP@NPC composite material according to claim 1, characterized in that, The iron source is ferric nitrate nonahydrate, the nickel source is nickel nitrate hexahydrate, and the organic ligand is 2-aminoterephthalic acid; the molar ratio of ferric nitrate nonahydrate, nickel nitrate hexahydrate and 2-aminoterephthalic acid is (1~2):(0.5~2):(1~1.5).

3. The method for preparing a FeNiP@NPC composite material according to claim 1, characterized in that, The acidic phosphorus source is phytic acid, and the aniline polymerization oxidative initiator is ammonium persulfate.

4. The preparation method of FeNiP@NPC composite material according to claim 3, characterized in that, The volume-to-mass ratio of phytic acid, aniline, and ammonium persulfate is (250~300) μL: (450~550) μL: (650~750) mg.

5. The method for preparing a FeNiP@NPC composite material according to claim 3, characterized in that, Step S2 further includes: first dispersing the organometallic coordination precursor and sodium dodecylbenzenesulfonate in deionized water, and then adding phytic acid, aniline and ammonium persulfate.

6. The method for preparing a FeNiP@NPC composite material according to claim 5, characterized in that, The mass ratio of the organometallic coordination precursor, sodium dodecylbenzenesulfonate and ammonium persulfate is (20~30):(60~65):(80~95).

7. The method for preparing a FeNiP@NPC composite material according to claim 1, characterized in that, The zeolite imidazole ester skeleton material is ZIF-8, and the mass ratio of the composite modified precursor to the zeolite imidazole ester skeleton material is 1:(7~10).

8. The method for preparing a FeNiP@NPC composite material according to claim 1, characterized in that, The calcination is a segmented calcination, specifically: the temperature is increased from room temperature to 500-600℃ at a heating rate of 5-10℃ / min and held for 1-1.5h, then the temperature is increased to 900-1000℃ and held for 1.5-2.5h, and the calcination atmosphere is nitrogen.

9. A FeNiP@NPC composite material, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.

10. The application of the FeNiP@NPC composite material according to claim 9 in a zinc-air battery.

Citation Information

Patent Citations

  • Hollow carbon nano tube loaded bimetallic heterogeneous phosphide electrocatalyst as well as preparation method and application thereof

    CN120376667A